PERBEDAAN PENGARUH PAPARAN MUSIK MOZART, BEETHOVEN, DAN CHOPIN SELAMA KEBUNTINGAN TERHADAP INDEKS APOPTOSIS SEL NEURON DI CEREBELLUM Rattus norvegicus BARU LAHIR - Dessy Hidayati Fajrin (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
The efforts that can be done to improve brain cells in the prenatal period is the provision of nutrients and good stimulation. Exposure to classical music such as Mozart, Beethoven, and Chopin music can increase the wave of brain activity. During pregnancy, Mozart music is proven to decrease the apoptosis of neuronal. Analyzing the difference of apoptosis neuronal of cerebrum and cerebellum of newborn baby of Rattus norvegicus that are exposed to the Mozart, Beethoven, and Chopin music, and that is not exposed to music during pregnancy.Laboratory experimental research, posttestonly control group design. Subjects were female pregnant Rattus norvegicus, grouped into 4 random groups: 1 control group and 3 treatments groups; with 6 samples each. Subjects were super ovulated, and 65 dB intensity of music is played for an hour at 20.00-21.00 on the subjects on 10th day of pregnancy. On 20th day of pregnancy, the mothers was dissected using SC technique. 2 heaviest newborn babies of Rattus norvegicus were taken.Statistical test concluded there wassignificant differences of apoptosis neuronal ofcerebellum of newborn babies of Rattus norvegicus among the exposure to Mozart, Beethoven, and Chopin music, and without the exposure to music with value of p=0,033 in cerebellum.In conclution, the exposure of Mozart’s music during pregnancy perform expression of BDNF cerebellum in the offspring-rat was higher than exposed Beethoven’s music, Chopin and not exposed to music.